52.6k views
1 vote
Solve for x.
-3 = 3(x-6) - 6x
Simplify your answer as much as possible.
X OO

2 Answers

4 votes

Answer:

x = -5

Explanation:

Performing the indicated multiplication, we get

-3 = 3x - 18 - 6x.

Combining the x terms, we get

-3 = -3x - 18

Combining the constants, we get

3x = 3 - 18, or 3x = -15.

Dividing both sides yields x = -5.

User Scott Boston
by
6.3k points
5 votes

Multiply the bracket by 3

-3= 3x-18-6x

-3= 3x-6x-18 - just rearranging.

-3= -3x-18

Move -18 to other side. Sign changes from -18 to +18.

-3+18= -3x-18+18.

15= -3x

Divide by -3 to get positive x .

15/-3= -3x/-3

x= -5

Answer: x= -5

User Paul Brinkley
by
6.0k points